PENGARUH KOMPRES DINGIN TERHADAP KEJADIAN INFLAMASI AKSES VASKULER PADA PASIEN YANG BARU MENJALANI HEMODIALISA DI RUANG HEMODIALISIS RSUD dr. HARYOTO LUMAJANG - Windy Arie Praherda; Suhari Suhari; Widya Addiarto (NHM PRESS, 2023)
Hemodialysis is the most common kidney replacement therapy performed by patients with chronic kidney failure. Patients undergoing hemodialysis must first have a vascular access installed to drain blood from the patient’s body to the machine. Complications that can occur in vascular access is inflammation at the insertion site. Nursing efforts to reduce inflammation are by using cold compresses. The purpose of this research was to analyze the effect of cold compresses on the incidence of vascular access inflammation. The research design was pre experimental with a one group pretest posttest research design. The population in this research were all patients who had recently undergone hemodialysis who experienced inflammation of the vascular access. The samples were taken using a purposive sampling technique so that 19 samples were obtained. Data collection tool to determine the incidence of inflammation using an observation sheet. The result of the Paired T-test before and after the cold compress intervention proved that there was a decrease in the incidence of inflammation vascular access with a value p = 0,000 and  < 0,05. It can be conclude there is an effect of cold compresses on the incidence of inflammation of the vascular access in patients who have just undergone hemodialysis. Based on the results of this study, it is hoped that it nurses are advised to apply cold compress therapy as an intervention to reduce inflammation of the vascular access of hemodialysis patients.